Perfil antropométrico e análise proteômica do plasma seminal: estratégia para identificação de marcadores moleculares da fertilidade em homens atendidos em um centro de referência em medicina reprodutiva em Fortaleza, Ceará - Cunha, Luana Mara Silva de Castro Pacheco da (2023)
Male infertility represents a public health problem with negative repercussions on male health, with central obesity and varicocele being risk factors that lead to significant seminal changes, making pregnancy impossible. In this sense, this thesis had two objectives: 1) to evaluate the association between anthropometric markers (BMI, WC) and clinical parameters, including the lifestyle of men undergoing reproductive treatment and 2) to identify biomarkers for male infertility based on the characterization Proteomics of seminal plasma from men attended at an assisted reproduction clinic. The study included 117 men attended at the reproductive medicine center from October 2019 to March 2020. Weight (kg) and waist circumference (cm) were measured and a socioeconomic and lifestyle form was applied. Semen collection was performed to obtain the seminal report and proteomic analysis. In research 1, 98 participants were divided into three groups and categorized by BMI, namely: eutrophic (n = 14), overweight (n = 56) and obese (n = 28). The mean age was 37.8 (6.8) years and the WC was 96.3 (15.3) cm. There was a significant association between BMI and WC (p<0.001), BMI and family diseases (p=0.017), highlighting obesity (p=0.017) and diabetes (p=0.008), as well as medication use (p=0.049). For research 2, we focused on the proteomic analysis where 19 men with a mean age of 35.9 (6.4) years were divided into 4 groups, normozoospermic (NZ) (n=5), varicocele and asthenozospermia (VAZ) (n= 4), varicocele and teratozoospermia (VTZ) (n=4) and, varicocele and oligoteratozoospermia (VOTZ) (n=6). 4,245 proteins were identified in seminal plasma, 724 of them in the NZ group, with emphasis on the most abundant ANX A3, PRDX1 and CRAC1. Then, the VAZ group with 886 proteins with emphasis on IGLC3, IGLC1 and H2BC1, the VOTZ group with 907 proteins, with emphasis on TUBB, MSLN and HEX and the VTZ group, with 1728 proteins, in which HSPA1, KIF5C and CLTCL1, identified as the most abundant. This study provided the association of BMI and familial diseases and medication use, as well as the first characterization of the seminal plasma proteome of men with normal seminal parameters and varicocele, in which it was possible to identify proteins and pathways associated with spermatogenesis, energy metabolism, fertilization, permeability of the reproductive tract and immunofertility. Keywords: male infertility, obesity, circumference waist, seminal plasma, varicocele, proteome.